APPLICATION OF VALUE ENGINEERING IN AFFORDABLE HOUSING IN INDIA - Sharma, Prashant; Srikonda, Ramesh (International Journal of Engineering Technologies and Management Research, 2021)
A major challenge for the Indian government is the rapid growth of the urban population, leading to housing shortages and poor urban living conditions. The current need-based housing shortage in the country is about 19 million units as per the 2011 census. The government has introduced many affordable housing schemes that focus on meeting the shortage of housing needs. Excess cost management needs to be planned from the initial stages of design during the building's project life. Value engineering is an effective problem-solving approach that minimizes prices while preserving and improving performance and quality requirements. Ve process's success lies in its ability to find ways to reduce redundant expenses while maintaining efficiency, reliability, performance, and other critical elements that reach or surpass the standards of the client. This study aims at understanding the application of value engineering in affordable housing to optimize cost, time and quality thus increasing overall value of the project. Two case studies of different scale of housing projects are considered, it has been found out that on replacing a material with similar functions, helps reduce the cost of the project and add to the value of the project. This research will provide an overview of benefits of strong value engineering and use of alternative materials to enhance the efficiency of a project.